The Role of Halal Certification and Brand Image in Increasing Consumer Trust (Case Study of MSMEs Crispy Masjef Bananas) - Arif Muhnidin; Rasta Kurniawati Br. Pinem (Newinera Publisher, 2024)
One of the MSME products in the city of Medan that has been certified halal is Pisang Crispy Masjef, founded in 2020 and quite well known among the people around Medan Johor for its crispy bananas and abundant toppings. The problem in this research is whether halal certification and brand image have an influence on increasing consumer trust and promoting Masjef Crispy Banana MSMEs, as well as what the owner's role is in increasing consumer trust. The objectives of this research are: (1) to know and analyze the effect of halal certification in increasing consumer confidence; (2) to explain and analyze the influence of brand image in promotion; and (3) to understand the role of the owner of Masjef Crispy Banana UMKM in increasing consumer trust through halal certification and brand image. The research method used in this study is descriptive quantitative. The research results show that halal certification and brand image have a significant effect on increasing consumer trust, with the t-count value of the halal certification variable being 4.963 and the t-count value of the brand image variable being 9.512, which is proven to be greater than the t-table value of 1.673. Furthermore, this research also indicates that the owner of the Crispy Masjef Banana UMKM plays a role in increasing consumer confidence by arranging halal certification and carrying out re-branding according to surveys and market demand, changing from